The impact of motivational interviewing on participation in childbirth preparation classes and having a natural delivery: a randomised trial. (10th November 2016) - Rasouli, M; AtashSokhan, G; Keramat, A; Khosravi, A; Fooladi, E; Mousavi, SA
Abstract : Objective: This study aimed to determine the effectiveness of motivational interviewing on women's participation in childbirth classes and their subsequent natural vaginal delivery. Design: Randomised controlled trial. Setting: Prenatal clinic of the Shohada Women's Hospital, Behshahr, Mazandaran, Iran. Population: This study was conducted with 230 nulliparous women. Participants were randomised into three groups, including 76 women in the motivational interviewing group, and 77 women in both the lecture and the control groups. Methods: Participants were assessed at three time points, including at baseline (16–19 weeks of gestation) and then following the intervention (at 21 and 37 weeks of gestation). The motivational interviewing group received two focus interviews and two telephone follow‐up sessions (at 3 and 6 weeks after the last session of motivational interviewing). The lecture group received a speech session. The control group received routine care service. Main outcome measures: Frequency of participation in childbirth preparation classes and mode of delivery. Results: Over 90% of women in the motivational interviewing group participated in childbirth preparation classes, whereas the rate of participation in the lecture and the control groups was 59.7 and 27.3%, respectively. The probability of maternal participation in childbirth classes in the motivational interviewing and in the lecture groups was 3.3 (95% CI 2.1–4.5) and 2.2 (95% CI 1.4–3.0) times the probability of maternal participation in the control group, respectively. Moreover, the intervention groups had 1.4 (95% CI 1.1–1.8) and 1.1 (95% CI 0.9–1.4) times the probability of natural delivery, compared with the control group. The frequency of natural delivery in motivational interviewing, lecture, and control groups was 68.4, 54.5, and 48.1%, respectively. The results showed a statistically significant difference between the mean scores for the awareness and attitude scores between the three groups in different time periods. Conclusion: We found that motivational interviewing can be a useful tool for encouraging pregnant women to attend childbirth preparation classes. Tweetable abstract: Motivational interviewing with nulliparous women is strongly associated with their attendance in childbirth preparation classes. Tweetable abstract: Motivational interviewing with nulliparous women is strongly associated with their attendance in childbirth preparation classes.